The impact of the organization of markets, old and new in the holy city of Karbala (journal Islamic sciences college, 2015)
Any city that has such a market and is organized, organized and establishedMiniAnd respectFreedom of expressionProfile.Conflict resolution and conflict resolutionPoliticalWhich affected the growth of some marketsAnd religious thThe search for the return of economic and cultural activity and the emigration of some othersCultural exchange and trade, which in turnAl-RifaieWe took the problem that we are experiencingMenia, the holy city of Karbala in the market organization, has suffered from fierce attacksEconomic and heritageeAs well as tourism and tourism, as it depends on the abundance of visitors, tourists and residents in terms of needs and motivationResourcesEconomic development. ComeIt is the primary focus of the market research communityEnglishNHExtend the method and the organization of the organization in Asquim, and believe that the author and the Arabs came out of the Bedouin to nFor you to market Yat season they claimAnd the name and number of the two pillars, and relied on the activity of the movementTourist and presenceThe visitors were in Via, and they swarmed inAnd the apostles of the Holy ProphetThe most sacred person who said in the footsteps of human beingsM): "Hussein YTo God Amio and Alo marking)DeafWho am I from Hussein I love God from.Hossein "dFitzo the IncomingElijahThe devotee who lives in Viya needs a spiritual soul from Nafat al-Husayn (Amiyo al-Salem), as well as the presence of YenIt was not an organizationMimp to meet the needs of the organization of affairs and actions and arrange the affairs of life, markets KmIndividuals attract visitorsAnd they shall call Haggaim, which shall baptize, and shall take the intercessions, from Minya to Eimeim, or takeWidgets and hearing aidsThe deceased in Mdenim,The visitor is very pleased if he goes to KarbalaMurad K.And is considered by needs and hearing.